1973
DOI: 10.1104/pp.51.6.1037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phenolic Acids on Ion Uptake

Abstract: The influence of naturally occurring phenolic acids on phosphate uptake by barley (Hordeum vulgare L. cv. Karlsberg) roots was examined using '3P-labeled phosphate. Without exception, all compounds tested, namely, benzoic, 2-hydroxybenzoic, 4-hydroxybenzoic, 3,4-dihydroxybenzoic, 3,4,5-trihydroxybenzoic, 4-hydroxy-3-methoxybenzoic, 4-hydroxy-3,5-dimethoxybenzoic, cinnamic, 2-hydroxycinnamic, 4-hydroxycinnamic, 3,4-dihydroxycinnamic, 4-hydroxy-3-methoxycinnamic, and 4-hydroxy-3,5-dimethoxycinnamic acids, inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1
2

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 17 publications
3
43
1
2
Order By: Relevance
“…In root tissue this involves a nonspecific increase in permeability to both cations and anions (3,5). Reference to the Goldman equation indicates that this increase in permeability and the resultant efflux of ions will affect E in two ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In root tissue this involves a nonspecific increase in permeability to both cations and anions (3,5). Reference to the Goldman equation indicates that this increase in permeability and the resultant efflux of ions will affect E in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…In a large number of reported cases, however, the modes of action of the allelopathic compounds (allelochemicals) are not understood. This paper reports further investigations into the mode of action of an important group of allelochemicals, phenolic acids.Earlier papers by Glass (3)(4)(5) have established that one ubiquitous group of phenolics, namely benzoic and cinnamic acids, are potent inhibitors of active K and Pi absorption by excised barley roots. The effect is readily reversible and the inhibitory capacity of the benzoic acids is strongly correlated with their lipid solubilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that the effects of boron deficiency were direct and not mediated by accumulation of phenolic compounds since ' a reversibly impaired ATP-ase has been isolated from boron-deficient plants under conditions which should remove any phenolics bound to the membrane' (my italics). However, exogenous phenolics can markedly inhibit uptake of both anions and cations by roots of barley and soy-bean (Glass, 1973(Glass, , 1974Glass and Dunlop, 1974;McClure, Gross and Jackson, 1978). It remains to be seen how increased levels of endogenous phenols, brought about by boron deficiency (see pp.…”
Section: The Metabolic Role(s) Of Boronmentioning
confidence: 99%
“…Addition of chelators to nutrient solutions can reduce metal activity and uptake (Foy, Chaney and White, 1978) but Wallace et al (1974) suggest that uptake of metal chelates by snap beans may account for the high levels of Cu, Co and Cd in plants raised on chelator ammended soils. Glass (1973Glass ( , 1974 demonstrated that in short-term experiments, uptake of K and phosphate was inhibited by phenolic compounds which strongly infiuenced cell membrane potentials. Glass and Dunlop (1974) support the hypothesis that phenolic infiuence on ion uptake is mediated through direct non-specific effects upon cell membrane permeability.…”
Section: Introductionmentioning
confidence: 99%